A Scoping Review of Trials Designed to Achieve Remission of Type 2 Diabetes with Lifestyle Intervention Alone: Implications for Sub-Saharan Africa - Duhuze Karera, M Grace; Wentzel, Annemarie; Ishimwe, MC Sage; Gatete, Jean de Dieu; Jagannathan, Ram; Horlyck-Romanovsky, Margrethe F; Sumner, Anne E (Diabetes, metabolic syndrome and obesity, 2023)
According to the International Diabetes Federation, sub-Saharan Africa is experiencing the highest anticipate increase in the prevalence of type 2 diabetes (T2D) in the world and has the highest percent of people living with T2D who are undiagnosed. Therefore, diagnosis and treatment need prioritization. However, pharmacological hypoglycemics are often unavailable and bariatric surgery is not an option. Therefore, the ability to induce T2D remission through lifestyle intervention alone (LSI-alone) needs assessment. This scoping review evaluated trials designed to induce T2D remission by LSI-alone. PubMed, Embase, Cochrane, and CINAHL databases were searched for trials designed to induce T2D remission through LSI-alone. Of the 928 identified, 63 duplicates were removed. With abstract review, 727 irrelevant articles were excluded. After full-text review, 112 inappropriate articles were removed. The remaining 26 articles described 16 trials. These trials were published between 1984 and 2021 and were conducted in 10 countries, none of which were in Africa. Remission rates varied across trials. Predictors of remission were 10% weight loss and higher BMI, lower A1C and shorter T2D duration at enrollment. However, LSI-alone regimens for newly diagnosed and established T2D were very different. In newly diagnosed T2D, LSI-alone were relatively low-cost and focused on exercise and dietary counseling with or without calorie restriction (~1500 kcal/d). Presumably due to differences in cost, LSI-alone trials in newly diagnosed T2D had higher enrollments and longer duration. For established T2D trials, the focus was on arduous phased dietary interventions; phase 1: low-calorie meal replacement (<1000 kcal/day); phase 2: food re-introduction; phase 3: weight maintenance. In short, LSI-alone can induce remission in both newly diagnosed and established T2D. To demonstrate efficacy in Africa, initial trials could focus on newly diagnosed T2D. Insight gained could provide proof of concept and a foundation in Africa on which successful studies of LSI-alone in established T2D could be built.